Execução coletiva dos direitos difusos, coletivos e individuais homogêneos reconhecidos em sentença face à efetividade da tutela jurisdicional - Lamblém, Gláucia Aparecida da Silva Faria (2015)
This study has the purpose of examining the limits of applicability of the procedural rules of the Code of Civil Procedure related to the execution of sentence in class action lawsuits. This is done through a reinterpretation of the constitutional principles of the process, from the perspective of maximum effectiveness of collective judicial protection because of the own protected material right. Considering that the effectiveness of judicial protection is closely connected to the implementation of judicial decisions, the topic is addressed in the context of execution of sentence in class actions for protection of diffuse, collective, and homogeneous individual rights. It is highlighted the judge's role in the fair adequacy of such rules to the concrete case. The study of execution of sentence under the collective jurisdiction is justified, since this leads the judicial decision to an end, being able to assess the practical impact of judicial protection. In this sense, the mass society and conflicts arising from it, allows violation to a plurality of rights, involving large numbers of subjects, thus requiring legal responses in accordance with the complexity of the factual situation. It is taken into account that the judicial response should not adhere to generic directions, requiring, therefore, the effective implementation of its controls, otherwise giving rise to the ineffectiveness of judicial protection. The theme of execution of sentence, interpreted in a broad sense, as all judicial decisions, shows fertile ground to scale the role of the judge and the influence of the executive mechanisms available on existing standards for the effectiveness of collective judicial protection. The examination of integrative rules of collective procedural microsystem, combined with those of the Code of Civil Procedure relating to the enforcement of court decisions and being in line with the constitutional principles of the process enables a true adequacy of the executive procedure in class actions such as to provide the effectiveness of collective judicial protection. In this context, the judge s role is essential to the effectiveness of judicial protection, not being limited to enforce the law and pronounce judgment on the merits, but to the exercise of a power of execution aimed to give effect to his/her own decisions